Entrepeneur Independence Model in Improving Entrepeneur's Performance in Lubuk Pakam District - Julita Julita; Nel Arianty; Muis Fauzi Rambe (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2021)
This study aims to improve entrepreneur's performance through entrepreneur's independence for business actors. This study uses the Research and Development (R & D) method, in line with the objectives to be achieved in this study, namely the development of an entrepreneur's independence model in increasing entrepreneur's business performance.The data analysis technique uses descriptive statistics and analyzes the entrepreneur's performance of business actors through the entrepreneur's independence model in the business in Lubuk Pakam District, Deli Serdang Regency through 9 small and medium business actors.From the results of the survey and the distribution of questionnaires conducted by the research team, the results of the research are, small and medium enterprises in Lubuk Pakam District do not have good entrepreneurial independence or business independence so they are not able and effective in running a business, so the results obtained have not as expected.